Comparison of mediating effects of air pollutants on urban morphology and urban heat Island intensity at block scale - Jiayu Fan; Xuegang Chen; Weihong Zhang; Mei Zhao; Xinlu Yang (Scientific Reports)
Abstract The urban heat island effect seriously challenges the sustainability and livability of urban development. Air pollutants (AP) may play a mediating role in the impact of urban morphology (UM) on the canopy layer urban heat island intensity (CLUHII) and the surface urban heat island intensity (SUHII). To verify this hypothesis, taking Urumqi as an example, we use the ridge regression model to reveal the differences in the impacts of UM and AP on the two types of urban heat island intensity (UHII). A structural equation model was established to verify the mediating effect of AP. The results show that: (1) There are differences in the optimal research units for UM and CLUHII and SUHII, which are 500 m and 300 m respectively. (2) Whether it is CLUHII or SUHII, the impact of two - dimensional urban morphology indicators are greater than that of three - dimensional urban morphology indicators. (3) There are similarities and differences in the impact of urban morphology indicators on the two types of UHII. The effects of standard deviation of building height, floor area ratio, and sky view factor on the two are opposite. (4) Air pollutants (PM10, PM2.5, NO2) have significant mediating effects between building density, impervious surface percent, green coverage ratio, mean building height, standard deviation of building height, floor area ratio, sky view factor, and the two types of UHII. This study provides a reliable reference for urban planning aimed at mitigating the urban heat island effect and air pollution.